2017
DOI: 10.1038/srep44306
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 Inhibitor and Estrogen Share Similar Efficacy Against Cardiac Ischemic-Reperfusion Injury in Obese-Insulin Resistant and Estrogen-Deprived Female Rats

Abstract: Estrogen deprivation aggravates cardiac injury after myocardial ischemia and reperfusion (I/R) injury. Although either estrogen or the dipeptidyl peptidase-4 (DPP-4) inhibitor, vildagliptin, reduces myocardial damage following cardiac I/R, their effects on the heart in obese-insulin resistant and estrogen deprived conditions remain unknown. Ovariectomized (O) rats (n = 36) were divided to receive either normal diet (NDO) or high-fat diet (HFO) for 12 weeks, followed by treatment with a vehicle, estrogen or vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 60 publications
1
21
1
Order By: Relevance
“…Estrogen treatment was prepared using estradiol powder (Sigma-Aldrich Co.) dissolved in ethanol and then mixed with sesame oil (Sigma-Aldrich Co.). The regular dose of estradiol used in this study was previously demonstrated to improve cardiometabolic status in ovariectomized female rats (Sivasinprasasn et al 2016(Sivasinprasasn et al , 2017. The NAC solution was prepared by mixing NAC powder with normal saline (NSS) using the concentration of NAC 40 mg per 200 μL of NSS.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 4 more Smart Citations
“…Estrogen treatment was prepared using estradiol powder (Sigma-Aldrich Co.) dissolved in ethanol and then mixed with sesame oil (Sigma-Aldrich Co.). The regular dose of estradiol used in this study was previously demonstrated to improve cardiometabolic status in ovariectomized female rats (Sivasinprasasn et al 2016(Sivasinprasasn et al , 2017. The NAC solution was prepared by mixing NAC powder with normal saline (NSS) using the concentration of NAC 40 mg per 200 μL of NSS.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…An echocardiograph (SONOS4500, Philips with S12 probe, Hewlett Packard) was used for collecting the data. Signals from pulsed-wave Doppler and M-mode echocardiography at the papillary muscle level were recorded (Sivasinprasasn et al 2017).…”
Section: Echocardiography Protocolmentioning
confidence: 99%
See 3 more Smart Citations